Finite Element Method (FEM) simulation of static and dynamic tensile test - Tan, Yi Zhi (Nanyang Technological University, 2020)
Tensile testing is utilised to work out a material’s mechanical behaviour under tension loading. It identifies if the material is suitable for engineering and design applications. For isotropic materials like Aluminium 6061-T6, uniaxial tension loading is applied in tensile tests to obtain the material’s properties of an initially crack-free specimen from stress versus strain curves acquired from experimental data. This project focuses on simulating two kinds of experiments, namely the Static Tensile Test and Dynamic Tensile Test to investigate the mechanical properties of Aluminium 6061-T6. The Static Tensile Tests are modelled after the physical experiments that can be conducted in the N3.2-B2-01, the Strength of Material Laboratory of Nanyang Technological University (NTU) using the Shimadzu AG-X plus 10kN Universal Testing Machine (UTM). The Dynamic Tensile Tests are modelled after the physical experiments using the Split Hopkinson Tensile Bar (SHTB) setup. The series of simulations are performed using the ANSYS software package, and the main software used are the ANSYS Spaceclaim to model the physical experiment and ANSYS Mechanical to perform the actual simulation. By using the known physical properties of Aluminium 6061-T6 alloys and results from experiments conducted from various authors and other FYP students, the validation of the FEM simulations can be identified using different parameters such as specimen geometry and impact velocities. Finally, recommendations were proposed to further capability studies and assessment of the simulations to increase accuracy and efficiency.